2023
DOI: 10.3390/computation11020028
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric Estimation of Range Value at Risk

Abstract: Range value at risk (RVaR) is a quantile-based risk measure with two parameters. As special examples, the value at risk (VaR) and the expected shortfall (ES), two well-known but competing regulatory risk measures, are both members of the RVaR family. The estimation of RVaR is a critical issue in the financial sector. Several nonparametric RVaR estimators are described here. We examine these estimators’ accuracy in various scenarios using Monte Carlo simulations. Our simulations shed light on how changing p and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Thus, RVaR 2.5%, 5% ≤ RVaR 1%, 5% ≤ RVaR 1%, 2.5% . Biswas and Sen (2023) and Müller et al (2022) found similar result. This result is in line with the expected; that is, lower significance levels are associated with greater protection.…”
Section: Univariate Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Thus, RVaR 2.5%, 5% ≤ RVaR 1%, 5% ≤ RVaR 1%, 2.5% . Biswas and Sen (2023) and Müller et al (2022) found similar result. This result is in line with the expected; that is, lower significance levels are associated with greater protection.…”
Section: Univariate Resultssupporting
confidence: 65%
“…Notice that improvements from univariate to multivariate models were reported, for instance, in Santos et al (2013) and Wang and Wu (2012). 3 Biswas and Sen (2023) is also closely related to the present paper since they performed a comparison of nonparametric estimators for the RVaR. However, unlike our study, Biswas and Sen (2023) examine estimators using Monte Carlo simulations, and they perform a backtesting exercise of RVaR forecasts inspired in the Acerbi and Szekely's test (Acerbi & Szekely, 2014).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations